Nestmate recognition in defense against nest invasion by conspecifics during swarming in a one-piece nesting termite. Issue 1 (December 2016) - Aguilera-Olivares, Daniel; Rizo, José; Burgos-Lefimil, Camila; Flores-Prado, Luis; Niemeyer, Hermann
Abstract Background In one-piece nesting termites, which nest and forage in a single piece of wood, soldier production increases during the swarming period, i.e. when the risk of invasion of their substrate and hence of their colony by dealates in search of a nesting substrate increases. InNeotermes chilensis, a one-piece nesting termite endemic to Chile, we hypothesized: i) that during swarming soldiers would defend their colony by showing higher aggressiveness toward non-nestmate than toward nestmate dealates, ii) that aggressiveness would negatively correlate with genetic relatedness of interacting soldier/dealate pairs and iii) that nestmate recognition would be based on differences in cues provided by cuticular compounds (CC) between nestmates and non-nestmate dealates. Methods The first hypothesis was tested using bioassays in which a soldier was confronted with a nestmate or a non-nestmate dealate; the second hypothesis by using microsatellites to assess genetic relatedness of the interacting pairs; and the third hypothesis using bioassays in which a soldier was confronted with a nestmate or a non-nestmate dead dealate with or without its CC and with dead dealates with interchanged CC between nestmate and non-nestmate. Results Soldiers were more aggressive toward non-nestmate than nestmate dealates, aggressiveness was inversely correlated with genetic relatedness of the interacting pair, and CC accounted for the differences in aggressiveness towards nestmate and non-nestmate dealates. Conclusions During swarming, soldiers ofN. chilensis protect their nest against invasion by non-nestmate conspecific dealates; discrimination is based on CC and aggressiveness correlates inversely with genetic relatedness of the interacting soldier/dealate pairs.